Women's Clothing and Adornment in the Fatimid State: A Historical Study in Egypt (358–567 AH/969–1171 AD) - Karim, Salah Atiya; Bashinah, Mohammed Omar (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This research addresses women's clothing and adornment during the Fatimid period, highlighting the cultural patterns and traditions related to women's attire. The study reviews the types of clothing used, such as head coverings and wraps, and analyzes the materials and techniques employed in their production. It also examines the impact of social classes on clothing and adornment styles, with a focus on the roles of concubines, entertainers, and peasant women. The research aims to highlight the historical development by tracing the evolution of clothing and adornment throughout the Fatimid rule, seeking to understand the role of these elements in defining the social and economic status of women in Fatimid society. The research involved a narrative and descriptive historical approach and used the American Psychological Association (APA) citation style. The research yielded several results, summarized as follows: Cultural impact was significant, as clothing and adornment represented a part of Fatimid cultural identity, influenced by religious and political factors, which contributed to the formation of new styles. Women utilized luxurious materials, such as colorful fabrics, jewels, crowns, and belts, especially among the upper classes, reflecting their social and economic status. Additionally, the colors and decorations used carried symbolic meanings, reflecting social status and various occasions, such as weddings and funerals.
Keywords: Fatimid State; Clothing; Adornment; Crown; Veil; Cloak